2016
DOI: 10.1002/ange.201609309
|View full text |Cite
|
Sign up to set email alerts
|

Eine monoanionische Arsenid‐Quelle: Decarbonylierung des 2‐Arsaethinolat‐Anions bei der Reaktion mit Stannylenen

Abstract: [6][7][8][9] Metathesereaktionen çffnen den Zugang zu verschiedenen Koordinationsverbindungen von Hauptgruppenelementen, [10] Actinoiden [11] und Übergangsmetallen [12][13][14] sowie zu Phosphaketen-Verbindungen der Gruppe-14-und Gruppe-15-Elemente (Silyl bis Plumbyl, [15,16] Germylenyl [17][18][19] und Phosphanyl, [20][21][22][23] C). Darüber hinaus wurde auch über Cycloadditionen mit Alkinen, [24] Ketenen und Carbodiimiden berichtet. [25,26] Unter diesen vielen Studien finden sich nur drei Beispiele,indenen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…[6a] Theinitial studies by this group showed that the CO moiety in (AsCO) À is released with greater ease than that in (PCO) À . [6] This can be understood taking into account the resonance structures A-C (Scheme 1) where C, (E ! CO) À ,h as as mall but significant contribution to the electronic ground state.Remarkably,Bertrand et al reported the substitution of the CO ligand when phosphaketenes of type R 2 P À P = C = Owere reacted with isocyanides,phosphanes, and heterocyclic carbenes.…”
mentioning
confidence: 99%
“…[6a] Theinitial studies by this group showed that the CO moiety in (AsCO) À is released with greater ease than that in (PCO) À . [6] This can be understood taking into account the resonance structures A-C (Scheme 1) where C, (E ! CO) À ,h as as mall but significant contribution to the electronic ground state.Remarkably,Bertrand et al reported the substitution of the CO ligand when phosphaketenes of type R 2 P À P = C = Owere reacted with isocyanides,phosphanes, and heterocyclic carbenes.…”
mentioning
confidence: 99%